Huber expands alumina-based range of thermally conductive additives for polyamides. Issue 12 (December 2018) - Unknown
Abstract : Huber Martinswerk, part of J.M. Huber Corp's Huber Engineered Materials division, has introduced Martoxid® TM-4250, the latest grade in its Martoxid TM-4000 series [ ADPO, December 2016] of alumina-based thermally conductive fillers specially designed for polyamides. The new additive is claimed to increase orientation-independent (isotropic) thermal conductivity in PA6 and PA66 up to 2.5 W/mK, both in-plane and through plane.